2011
DOI: 10.1051/0004-6361/201117055
|View full text |Cite
|
Sign up to set email alerts
|

The HARPS search for Earth-like planets in the habitable zone

Abstract: Abstract. In 2009 we started an intense radial-velocity monitoring of a few nearby, slowly-rotating and quiet solar-type stars within the dedicated HARPS-Upgrade GTO program. The goal of this campaign is to gather very-precise radial-velocity data with high cadence and continuity to detect tiny signatures of very-low-mass stars that are potentially present in the habitable zone of their parent stars. Ten stars were selected among the most stable stars of the original HARPS high-precision program that are unifo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
248
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 268 publications
(271 citation statements)
references
References 35 publications
18
248
5
Order By: Relevance
“…As shown hereafter, this could be the case for Gl 581 c (Udry et al 2007;Mayor et al 2009;Forveille et al 2011) and HD 85512 b (Pepe et al 2011), the only two confirmed planets having masses that are compatible with a terrestrial planet (M p < ∼ 7−8 M ⊕ ; although defining such a mass limit is questionable) and that lie beyond the inner edge of the classical habitable zone but receive a moderate stellar flux, F /4 < 1000 W/m 2 . These planets lie even closer to the star that the inner edge of the limits set by Abe et al (2011) for land planets.…”
Section: Beyond the Runaway Greenhouse Limitmentioning
confidence: 89%
“…As shown hereafter, this could be the case for Gl 581 c (Udry et al 2007;Mayor et al 2009;Forveille et al 2011) and HD 85512 b (Pepe et al 2011), the only two confirmed planets having masses that are compatible with a terrestrial planet (M p < ∼ 7−8 M ⊕ ; although defining such a mass limit is questionable) and that lie beyond the inner edge of the classical habitable zone but receive a moderate stellar flux, F /4 < 1000 W/m 2 . These planets lie even closer to the star that the inner edge of the limits set by Abe et al (2011) for land planets.…”
Section: Beyond the Runaway Greenhouse Limitmentioning
confidence: 89%
“…As205a back with AS 205A. Pepe et al (2011), using high-resolution spectroscopy, published the Keplerian solutions of two orbiting planets around HD192310. The dispersion of their RV measurements, however, had a rms of only 2.6 ms −1 over a 6.5-year interval.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…Our own study detected variations in the HD192310 RV profile with a standard deviation of ≤11 ms −1 over 4 years of observations. Although it was beyond our detection limit we tried nevertheless to adjust the Keplerian solutions of Pepe et al (2011) to the variations observed. The lack of consistent fits implied that the dispersion in our RV data was instead associated with the internal uncertainty of our method.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…The spin-orbit angle measurement may be helpful in modelling the planetary orbital evolution. The High Accuracy Radial-velocity Planet Searcher (HARPS, Mayor et al 2003), installed in 2002 on a 3.6 m telescope at the La Silla Observatory (Chile), has demonstrated a high efficiency for detecting lowmass exoplanets and for constraining their masses and orbital parameters, thanks to its sub-1 m/s RV stability (Pepe et al 2011).…”
Section: Introductionmentioning
confidence: 99%